The Influence of Make a Match Type Cooperative Learning Model on Student Learning Outcomes in Theme 2 Subtheme 2 about the Importance of Clean Air for Respiration in Class V Students of UPTD SD 124385 Pematang Siantar - Putri Azhari; Theresia Monika Siahaan; Desi Sijabat (MultiTech Publisher, 2023)
The background to this research is based on observations made by researchers in class V UPTD SD Negeri 124385 Pematang Siantar, namely that teachers still use conventional learning models, resulting in low student learning outcomes. From the problems described above, it is necessary to find a solution, namely by implementing the Make a Match type cooperative learning model. This model is suitable for use in all subjects and this model is suitable for use in class V because this learning model invites students to work together and trains students' courage to appear in front of the class so that student learning outcomes can improve. This research used a pre-experimental method with a one group pretest-posttest design with a sample of 25 students. Based on the results of the data analysis test used, the Hypothesis Test results obtained were Tcount = 17.321 and Ttable = 2.064 with Tcount>Ttable= 17.321>2.064, so Ho was rejected and Ha was accepted. With this explanation, it can be concluded that there is an influence of the Make a Match Type Cooperative learning model on student learning outcomes in class V UPTD SD Negeri 124385 Pematang Siantar.